Exploring teacher competencies in early language education: Perspective of MA pedagogy students - Szuchalska, Anna (Neofilolog, 2025)
The article aims at exploring students’ perceptions of the significance of particular teachers’ competencies in early language education. In the first part, a literature review synthesizing diverse definitions of teacher competencies based on varied criteria is presented. The second part depicts the results of a quantitative study involving a survey undertaken at the University of Bialystok, with 54 fourth-year pedagogy students majoring in early education participating. The survey instrument comprised closed-ended questions categorized into six competencies. The findings revealed that, among psychological and pedagogical competencies, skills and knowledge in fostering student motivation were deemed vital (59.3%). Educational competencies highlighted the significance of teacher’s empathy, enthusiasm, and optimism (68.5%), while substantive competencies emphasized the importance of using the foreign language during lessons (63%). Intercultural competencies highlighted the importance of teacher’s tolerance and openness (65%), and methodological and didactic competencies identified knowledge and skills in the concept of early school foreign language teaching as critical (53.7%). Among diagnostic competencies, the ability to interpret and evaluate lessons, observe and assess student involvement in linguistic activities, and recognize and understand errors were equally important (51.9%). The research outcomes offer valuable insights into the perspectives of MA pedagogy students, shedding light on the competencies they deem essential for effective early language education.